Kinetics and mechanism of hydrolysis of N-amidomethylsulfonamides - Iley, J (2015)
The kinetics of the hydrolyses of secondary and tertiary N-amidomethylsulfonamides were studied at 50 degreesC. Both types of N-amidomethylsulfonamide hydrolyse through acid- and base-catalysed processes, as indicated by the pH-rate profiles. The order of reactivity for the acid-catalysed pathway implies a mechanism involving protonation of the amide followed by expulsion of a neutral amide and formation of a sulfonyliminium ion. In the base-catalysed region, compound 5c, which is substituted at both amide and sulfonamide nitrogen atoms, hydrolyses by nucleophilic attack of hydroxide ion at the amide carbonyl carbon atom to form benzoic acid and a sulfonamide. In contrast, compound 5b, which contains a sulfonamide NH group, hydrolyses to benzamide and sulfonamide products by an E1cb(rev) mechanism involving ionisation of the sulfonamide. Compound 5a, which contains an amide NH, also hydrolyses to sulfonamide and amide products, probably by an E2 mechanism.